ASSET STRUCTURE, DEBT MANAGEMENT AND EFFICIENCY ON COMPANY VALUE THROUGH PROFIT PERFORMANCE (Case Study of a Manufacturing Company Listed on the Indonesian Stock Exchange) - Fatimah, Nur Itha; Laba, Abd. Rakhman; Nohong, Mursalim (Scientium Management Review, 2022)
This study aims to analyze the effect of asset structure, debt management and efficiency on firm value with earnings performance as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange. The data analysis technique uses SPSS and the Sobel Test and the data source used is secondary data in the form of financial reports of manufacturing companies for the 2014-2021 period. The type of data used is quantitative data with data collection techniques, namely documentation. The results of this study indicate that in the model 1 test it can be concluded that asset structure has no effect on earnings performance, while debt management has a negative and significant effect on earnings performance and efficiency has a positive and significant effect on earnings performance. And the results for the model 2 test, namely asset structure and efficiency have no effect on firm value while debt management and earnings performance have a positive and significant effect on firm value. For model 3 test results, namely asset structure has no effect on firm value when mediated by earnings performance. Meanwhile, debt management and efficiency have an influence on firm value when mediated by earnings performance.